2020
DOI: 10.5606/tgkdc.dergisi.2020.18439
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of early rib fixation for clinical outcomes of flail chest patients in intensive care unit

Abstract: Bu çalışmada yelken göğüs hastalarında konservatif ve cerrahi stabilizasyon yaklaşımlarının klinik sonuçları karşılaştırıldı ve erken redüksiyonun etkisi araştırıldı. Ça lış m a pla nı: Mart 2013-Aralık 2017 tarihleri arasında erken kaburga fiksasyonu yapılan yelken göğüslü 34 hasta (23 erkek, 11 kadın; ort. yaş 43.7±12.1 yıl; dağılım 20-74 yıl) cerrahi grubuna ve Şubat 2012-Aralık 2017 tarihleri arasında konservatif yaklaşım ile takip edilen yelken göğüslü 29 hasta (19 erkek, 10 kadın; ort. yaş 45.7±15.8 yıl;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Quality of life (QOL) was compared between groups in eight studies, but there were significant inconsistencies between measurement scales, and quantitative analysis could not be performed for this subjective clinical outcome. 9,28,37,38,47,48,57,62 A range of scales were used to assess QOL, including the Short Form 36, QOL Scale and EQ-5D-5L survey. Four studies 28,38,57,62 found a statistically significant benefit of surgical fixation on QOL but the other papers found no benefit.…”
Section: Other Outcome Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Quality of life (QOL) was compared between groups in eight studies, but there were significant inconsistencies between measurement scales, and quantitative analysis could not be performed for this subjective clinical outcome. 9,28,37,38,47,48,57,62 A range of scales were used to assess QOL, including the Short Form 36, QOL Scale and EQ-5D-5L survey. Four studies 28,38,57,62 found a statistically significant benefit of surgical fixation on QOL but the other papers found no benefit.…”
Section: Other Outcome Measuresmentioning
confidence: 99%
“…9,28,37,38,47,48,57,62 A range of scales were used to assess QOL, including the Short Form 36, QOL Scale and EQ-5D-5L survey. Four studies 28,38,57,62 found a statistically significant benefit of surgical fixation on QOL but the other papers found no benefit. Pain was also measured in 13 studies using a range of scoring systems, including the Visual Analog Scale (VAS), numerical pain score, and questionnaires.…”
Section: Other Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, another study reported that HLOS, ICU LOS, duration of mechanical ventilation, and mortality were higher in the conservative group compared with those managed surgically (p < 0.001, p < 0.001, p < 0.001, and p = 0.027, respectively) [ 23 ]. However, there was no statistical difference in complications such as pneumonia or sepsis between patient groups [ 23 ].…”
Section: Reviewmentioning
confidence: 99%
“…Balcı et al preferred titanium plate for this purpose and found that the material did not interfere with the visualization in thoracic CT and MRI taken after the plate application [10].…”
Section: Locking Plates (Figurementioning
confidence: 99%